Latency model of neighbor discovery based on Bluetooth low energy 5.0 - Bingqing LUO; Peipei WANG; Zhengkang WANG; Zhixin SUN (Tongxin xuebao)
For Bluetooth low energy neighbor discovery protocol, it was usually difficult to assess the discovery latency performance.A latency performance model of neighbor discovery based on Chinese remainder theorem for Bluetooth 5.0 standard was proposed.A mathematical relationship between the discovery latency and key parameters was put forward, including advertising interval, scan interval and scan window.The effect of different parameter configurations on the neighbor discovery latency was verified.Experimental results show that the model can effectively predict the delay peak under the influence of parameter configuration, and provide parameter configuration verification and guidance for different application scenarios.